Guidelines for Feminist HCI in practice: How far are we? - de Oliveira Freires, Maria Isabele; Noronha Monteiro, Kellen Raizy; Rodrigues de Sena, Geslâne; de Araújo Silva, Joana Ranikelly; da Silva Pinheiro, Valéria Maria; Marques, Anna Beatriz (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Feminist HCI aims to explore how gender relations shape the use, interaction, and design of technologies, and how we can address computational issues without perpetuating the marginalization of women or any other groups. Despite its relevance, recent research has identified indications that the quality criteria proposed by Feminist HCI are not widely adopted. Thus, this research aims to identify guidelines that support interaction design and user interface according to Feminist HCI principles. To this end, we conducted a Systematic Literature Mapping(SLM). As a result, we identified guidelines for HCI design regarding the collection and analysis of gender-sensitive data, the adoption of inclusive design strategies, and public engagement. On the other hand, we found few guidelines for interface design in practice, such as the use of information that does not reinforce harmful gender stereotypes. Although the works point out the benefits of Feminist HCI, such as promoting inclusion, contributing to equity, and preventing stereotypes, there are still many challenges, such as the need for further knowledge deepening, lack of interest in creating inclusive guidelines, and lack of consensus regarding criteria and practices. We noted that there are still no consolidated guidelines for the adoption of Feminist HCI in interactive systems design, which represents barriers to its adoption in practice.